Las limitaciones del Parlamento recién constituido durante la prorrogatio gubernamental - Gómez Corona, Esperanza (Revista de Derecho Político, 2016)
Resumen: Mucho se ha escrito sobre el sentido y las limitaciones del gobierno en funciones, instituto necesario porque la labor de gobierno no puede paralizarse por la sucesión natural de titulares al frente del mismo. El recurso a la prorrogatio de los órganos constitucionales sigue siendo válido para explicar este fenómeno. Menos interés ha suscitado el papel del Parlamento válidamente constituido tras la celebración de elecciones, en el tiempo que media entre esa constitución y la investidura del titular de la Presidencia del Gobierno. En las páginas que siguen abordaremos esta última cuestión, tratando de dilucidar si el sistema parlamentario de gobierno presente entre nosotros también en las Comunidades Autónomas introduce alguna variante en el funcionamiento parlamentario, más allá del derivado por las propias limitaciones gubernamentales del Ejecutivo en funciones. Abstract: Much has been written about the sense and limitation of the caretaker Government, deemed a necessary body since the governmental tasks may not be paralyzed due to the natural succession thereof. Resourcing to an extension (prorrogatio) of the mandate of constitutional bodies as caretakers still stands as a valid explanation of this phenomenon. The role of the Parliament validly constituted through elections during the vacatio leading to the appointment of the new president has attracted less interest. This work aims at addressing this understudied issued in an attempt to elucidate whether the Spanish parliamentary system of government, operating both at the State and regional levels, introduces any variant in the functioning of the Parliament beyond the common limitations of the caretaker Government. Summary: I. Preliminary. II. Outgoing government. II.1 Outgoing state government. II.2 Outgoing autonomic government. III. The limitations of the new elected Parliament during the extended mandate of the caretaker government. III.1 Internal proceedings. III.2 Parliamentary functions. IV. Concluding remarks